Sequence-based differentiation of strains in the Mycobacterium avium complex. - Frothingham, R (1993)
The complete 16S-23S rDNA internal transcribed spacer (ITS) was sequenced in 35 reference strains of the Mycobacterium avium complex. Twelve distinct ITS sequences were obtained, each of which defined a "sequevar"; a sequevar consists of the strain or strains which have a particular sequence. ITS sequences were identified which corresponded to M. avium (16 strains, four ITS sequevars) and Mycobacterium intracellulare (12 strains, one ITS sequevars). The other seven M. avium complex strains had ITS sequences which varied greatly from those of M. avium and M. intracellulare and from each other. The 16S-23S rDNA ITS was much more variable than 16S rDNA, which is widely used for genus and species identification. Phylogenetic trees based on the ITS were compatible with those based on 16S rDNA but were more detailed and had longer branches. The results of ITS sequencing were consistent with the results of hybridization with M. avium and M. intracellulare probes (Gen-Probe) for 30 of 31 strains tested. Serologic testing correlated poorly with ITS sequencing. Strains with the same sequence were different serovars, and those of the same serovar had different sequences. Sequencing of the 16S-23S rDNA ITS should be useful for species and strain differentiation for a wide variety of bacteria and should be applicable to studies of epidemiology, diagnosis, virulence, and taxonomy.